Peran job crafting dan work engagement sebagai pemediasi pengaruh perceived organizational support terhadap adaptive performance - Lesi Ardita; Dwiarko Nugrohoseno (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Human resources become one of the critical determinants in global developments, which are full of competition. Organizations need to pay attention to the quality of their employees, both in terms of the quality of knowledge and skills, career, and level of welfare, to increase employee performance and motivation to give all their abilities in achieving organizational goals with perceived organizational support. The support provided by the organization will have an impact on adaptive performance. Job crafting and work engagement are essential to achieve adaptive performance. This study uses quantitative research. The number of research samples, 81 employees, was determined based on proportionate stratified random sampling for data collection using a survey by distributing questionnaires online. The study's results prove that perceived organizational support has a significant positive effect on adaptive performance, perceived organizational support has a significant positive effect on job crafting, and perceived organizational support has a significant positive effect on work engagement. Job crafting does not affect adaptive performance. Work engagement has a significant positive effect on adaptive performance. Job crafting does not mediate the effect of perceived organizational support on adaptive performance. Job crafting mediates the effect of perceived organizational support on adaptive performance partially. The management must support the employee by motivating and giving them authority to solve their job in the organization.